Dietary survey of poultry egg intake among residents in Kunming city, southwest China - Wang, Rui; Wu, Yugao; Zhang, Chenxi; Liang, Chengyao; Xia, Xiran; Gao, Ximan; Fang, Jing (Frontiers in Nutrition, 2024)
Background For almost all people, eggs can be a wholesome addition to the diet. However, there is insufficient applicable data to evaluate the poultry egg intake of people in the city of Kunming located in southwest China. Objectives To understand the situation of egg consumption among local residents in Kunming via a dietary survey. Methods Residents living in three places of Kunming were chosen using a multi-stage random sampling method. The recall methods of 3-day food intake and 1-month food intake frequency were used to assess the quantity and frequency of poultry egg dietary intake of local people. Results Of the 1,118 respondents, 565 (50.54%) were female and 553 (49.46%) were male with age range 0.5–91 years old. Egg consumption was widespread among the survey respondents with 88.01% reporting hen egg ingestion, but the dietary intake of other poultry eggs such as duck, quail, and goose eggs were much less frequent. The medium daily intake of hen eggs was 20.00 g/d with greater amount of hen egg consumption in older age groups. However, when calculated on a body-weight basis, the median amount of hen eggs consumed daily per kilogram of body weight for all survey respondents was 0.47 g/kg/d whereas this indicator for children was 1.33 g/kg/d, becoming the greatest among all age groups. Conclusions Our study obtained a better understanding of poultry egg intake among residents in Kunming city and calculated the egg intake kilogram of body weight that can be a useful reference to inform the development of more accurate dietary recommendation. These results also provide basic data for nutrition monitoring and dietary exposure risk assessment of poultry egg intake.